Interpreting “Translanguages” in Transnational Women’s Literature: Socially Situated Perspectives and Feminist Close-Readings - Adelina Sánchez-Espinosa; Séamus O’Kane (Social Sciences, 2025)
This article explores the potentialities of “translanguages” as a lens for interpreting transnational women authors whose writing navigates multiple languages. By “translanguages”, we refer to the generation of a collage that results either from the writer’s alternation of various languages within the same work or from their concoction of a language of their own that reappropriates the contents and expressions of various source languages. We will illustrate our tenets by exploring case studies from Assia Djebar and Maxime Garcia Diaz. By resorting to feminist close-reading methodology, we intend to interrogate the possibilities of interpretation (and their limits) from a socially situated position. This, in turn, involves our approach to how the authors’ multiple languages interact and operate upon one another to create meaning and, last but not least, our analysis of the extent to which the transnational and translingual position of these authors shapes our own situated interpretations of the texts as readers.